Why ethics in research are crucial? - Abbas, Fathelrahman A.; Babikir, Mohamed O.; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed (American-Eurasian Network for Scientific Information (AENSI), 2012)
Ethical norms are so everywhere that one might be tempted to consider them as simple rational. Most civilizations use laws to implement widely accepted moral standards and legal rules. It is important to know that ethics and law are not the same. An act may be lawful but immoral/unethical or unlawful but moral/ethical. There are a number of reasons why it is essential to stick to ethical norms in conducting research. First, is to support the aims of research, such as knowledge, truth, and avoidance of error. For example, preventions of fabricating, falsifying, or misrepresenting research data support the truth and avoid error. Second, ethical standards promote the values that are vital to collaborative work, such as trust, accountability, joint respect, and fairness since research usually involves cooperation and coordination among many researchers in a mixture of disciplines and institutions. For example, many ethical standards in research, such as copyright, patenting policies, data sharing policies, and confidentiality rules in peer review, are deliberated to protect intellectual property interests as well as encouraging collaboration. Third, some ethical norms help to guarantee that researchers can be held responsible to the public. For instance, federal policies on research misconduct, conflicts of interest, the human subjects’ protections, and animal care and use are necessary in order to make sure that researchers who are funded by public money can be held accountable to the public. Fourth, ethical norms in research also help to build community support sustainability for research. Fifth, many of the ethical standards of research promote a variety of other moral and social values, such as human rights, animal welfare and compliance with the law, health and safety. Ethical descends in research can significantly harm the whole society and animal subjects. For example, a researcher who fabricates data in a clinical trial may harm or even kill patients. Also a researcher who fails to stand for guidelines and regulations relating to radiation or biological safety may endanger health and safety of himself, staff and students.